COUPLED FIXED POINT THEOREMS FOR GENERALIZED $α-ψ$-CONTRACTIVE MAPPINGS IN PARTIALLY ORDERED METRIC-TYPE SPACES - Hieu, N. T.; Hang, V. T. L. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we state some coupled fixed point theorems for generalized $α-ψ$-contractive mappings in partially ordered metric-type spaces. In addition, some particular cases and consequences of our theorems are given. Moreover, we give some examples to illustrate the obtained results.